2010
DOI: 10.1111/j.1464-410x.2010.09287.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the period between biopsy and diffusion‐weighted magnetic resonance imaging on cancer staging in localized prostate cancer

Abstract: Study Type – Diagnosis (exploratory cohort)
Level of Evidence 2b OBJECTIVES To investigate whether there are any differences between preoperative magnetic resonance imaging (MRI) and the final pathology results, based on the time between biopsy and preoperative MRI, as there are reports recommending ≥3 weeks after a prostate biopsy, primarily because haemorrhaging interferes with the interpretation of MRI. PATIENTS AND METHODS Between December 2007 and December 2008, we retrospectively analysed 69 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Second, several studies have reported that post-biopsy hemorrhaging diminishes with time 3,6,11. We also observed a statistically significant negative correlation between the sum of the hemorrhage score and the time from the biopsy in our previous and current study 7. However, some authors argue that post-biopsy hemorrhaging is not significantly reduced until 55 days after the biopsy 12,13.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Second, several studies have reported that post-biopsy hemorrhaging diminishes with time 3,6,11. We also observed a statistically significant negative correlation between the sum of the hemorrhage score and the time from the biopsy in our previous and current study 7. However, some authors argue that post-biopsy hemorrhaging is not significantly reduced until 55 days after the biopsy 12,13.…”
Section: Discussionsupporting
confidence: 65%
“…In this study, using multiparametric MRI, the timing of MRI did not affect the accuracy of PCa staging. Because multiparametric MRI usually has a greater sensitivity and specificity than conventional MRI, we believe that interpretation of MRI is less influenced by post biopsy hemorrhage 7,12,14,15. However, if the institute uses conventional MRI rather than multiparametric MRI for PCa staging, rectal compression may reduce the development of intraprostatic hemorrhage at biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, 8 post-biopsy hemorrhages were detected via magnetic resonance imaging up to 57 days after the biopsy and the total hemorrhage score was negatively correlated to the time from the biopsy. Our greater EBL in the surgery group within the 2 weeks after the biopsy might result from post-biopsy hemorrhage.…”
Section: Discussionmentioning
confidence: 91%
“…3,4,5 Other studies however, have found no significant difference in analysis and staging attributable to the period between the diagnostic biopsy and staging MRI. 6 Accurate OSCC staging is essential to provide patients and clinicians with information necessary to discuss and formulate critical treatment decisions. 7,8 This small cohort of patients with tongue OSCC demonstrates that undertaking biopsies before the staging MRI does not appear to compromise the accuracy of pre-treatment staging.…”
Section: Discussionmentioning
confidence: 99%